2017
DOI: 10.1177/0300060516685513
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone potentiates the antitumor effects of doxorubicin on gastric cancer cells via inhibition of STAT3 activity

Abstract: ObjectiveTo investigate the synergistic effects of cryptotanshinone (CPT) and doxorubicin (DOXO) on induction of apoptosis in human gastric cancer cells and the mechanisms.MethodsCell proliferation and apoptosis were detected using the CCK8 assay and AnnexinV/PI staining, respectively. Western blotting was used to determine the levels and phosphorylation of proteins encoded by STAT3-regulated genes and the cleaved forms of caspases and PARP.ResultsCPT significantly potentiated the antiproliferative effect of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Firstly, the efficacy of the investigated compound is relatively low as reflected by the proliferation assay. Nevertheless, based on our data and one publication 62 , the inhibition potency of ICTS was stronger than cryptotanshinone in SGC-7901 and MKN-45 cells. Different inhibitory effects of ICTS on different gastric cancer cells could be due to their discrepant differentiation potentials and cell types, which would be explained by further related studies.…”
Section: Discussionsupporting
confidence: 61%
“…Firstly, the efficacy of the investigated compound is relatively low as reflected by the proliferation assay. Nevertheless, based on our data and one publication 62 , the inhibition potency of ICTS was stronger than cryptotanshinone in SGC-7901 and MKN-45 cells. Different inhibitory effects of ICTS on different gastric cancer cells could be due to their discrepant differentiation potentials and cell types, which would be explained by further related studies.…”
Section: Discussionsupporting
confidence: 61%
“…Quercetin was reported to enhance the sensitivity of breast cancer cells to doxirubicin by downregulating p-Akt expression arising from increased expression of PTEN (18). Cryptotanshinone enhanced the anticancer activity of doxirubicin in gastric cancer (GC) cells via STAT3 inactivation and suppression of STAT3-regulated antiapoptotic gene expression (19). Taken together, these agents serve as adriamycin sensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptotanshinone (CTT) is extracted from the root of Salvia miltiorrhiza Bunge (Danshen) and has numerous pharmacological effects, including antioxidant, anti-hyperlipidaemia, anti-inflammation and anti-diabetes effects [14,15]. Moreover, numerous studies have shown that CTT exhibits activities against a variety of human cancers in vitro and in vivo and can be used for the management of human leukaemia, colorectal cancer, pancreatic cancer, breast cancer, prostate cancer, liver cancer, and gastric carcinoma [16][17][18]. However, the potential effect of CTT on bladder cancer and its mechanism remain unknown.…”
Section: Introductionmentioning
confidence: 99%